Transformasi Toko Kelontong Konvensional Menjadi Toko Kelontong Masa Kini Pada SRC Tata di Bandar Lampung - posroha, david; Ardansyah (Fakultas Ekonomi Universitas 45 Surabaya, 2023)
The purpose of this case was to find out how to Tata's grocery store changed to Sampoerna Retail Community (SRC). Find out what applications have been provided by PT HM Sampoerna for retail stores in attracting people to shop for their daily needs so that Sampoerna Retail Community (SRC) Tata can compete with other MSMEs. This type of research uses qualitative research by selecting Sampoerna Retail Community (SRC) Tata and 3 informants who are considered to have opinions and information regarding the Transformation of Conventional Grocery Stores into Today's Grocery Stores at SRC Tata in Bandar Lampung. Data collected in the form of: Documentation and in-depth interviews with informant source. The results of this case to tell that Sampoerna Retail Community (SRC) is a program launched by PT HM Sampoerna Tbk to assist and foster retailers in managing their stores in developing digitalized businesses to overcome high competition between MSMEs, which is the first in Medan in 2008 and then in 2017, Toko Tata joined Sampoerna Retail Community (SRC) until now using applications (Come on SRC Shop, Come on SRC Grocery, Come on Cashier and Pojok Pay) made by SRC himself.